Program Bicara Santai: cabaran, etika dan terokai dunia maya dengan al-Quran / Nadiah Mohamed and Norlis Osman - Mohamed, Nadiah; Osman, Norlis (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
On 23rd September 2020, FSKM KP organized a program called “Program Bicara Santai: Cabaran, Etika Dan Terokai Dunia Maya Dengan Al-Quran”. Three panels were invited to the program to share with the audience the importance of being safe in the cyberworld and role of science in our everyday life and the relevancy to Quran. The topics were chosen to stimulate interests of STEMS to students and also as public awareness. The first panel, Elina Mubin, an Executive of Outreach and Corporate Communications at Cybersecurity Malaysia, discussed issues of digital literacy in “Always Wise, Always Safe: Are You Digital Fluent. Mrs Elina stressed on how parents should be aware of ways to make sure the Internet is safe for their children and tips on monitoring their children’s surfing activity.